Advanced Information Systems Engineering Workshops : CAiSE 2012 International Workshops, Gdańsk, Poland, June 25-26, 2012 : Proceedings - Baje, Marko (edición); Eder, Johann (edición) ((Lecture Notes in Business Information Processing ;)
Contiene una selección de ponencias presentadas en ocho de los diez talleres llevados a cabo como parte de la 24° Conferencia Internacional de Ingeniería de Sistemas de Información Avanzados: 1) WISSE: Workshop on Information Systems Security Engineering; 2) ONTOSE: Workshop on Ontology, Models, Conceptualization and Epistemology in Social, Artificial and Natural Systems; 3) IWSSA: Workshop on System/Software Architectures; 4) HC-PAIS: Workshop on Human-Centric Process-Aware Information Systems; 5) GRCIS: Workshop on Governance, Risk and Compliance in Information Systems; 6) EOMAS: Workshop on Enterprise and Organizational Modeling and Simulation; 7) BUSITAL: Workshop on Businness/IT Alignment and Interoperability; 8) AgilES: Workshop on Agility of Enterprise Systems.